analyze the effect of Self-Actualization and Awards simultaneously on the Work Achievement of Teachers of SMP Negeri 6 Tanjungpinang. - Maryati yati ati (STIE PEMBANGUNAN TANJUNGPINANG, 2020)
This study aims to analyze the effect of Self-Actualization and Awards simultaneously on the Work Achievement of Teachers of SMP Negeri 6 Tanjungpinang. This research uses quantitative descriptive methods. Data analysis with multiple linear regression with the help of SPSS software version 22. The results showed Y = -4,230 + 0.808 X1 + 0.191 X2 and the value of R2 = 0.722 or 72.2%. T test results on the variable self-actualization (X1) on work performance (Y) obtained tcount (9,051)> ttable (2,035) and has a significance of 0,000 which is smaller than 0.05. T test results on the award variable (X2) on work performance (Y) obtained tcount (2,039)> ttable (2,035) and has a significance of 0.049 which is smaller than 0.05. The results showed that the variables of self-actualization and rewards partially or simultaneously had a positive and significant effect on the Work Achievement of Teachers of SMP Negeri 6 Tanjungpinang. With the contribution of Adjusted R Square of 72.2% work performance is influenced by self-actualization and rewards. Keywords: Self Actualization, Rewards, Work Achievement